VALUES OF LEADERSHIP UMAR BIN KHATTAB AND GENERATION Z ERA - Nursalim, Eko; Fitria, Nur Aidila (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The rise of internet use is certainly one of the causes of character change in Generation Z. People in Generation Z were born at a time when technology spread across the world, therefore their familiarity with gadgets has a significant influence on their personality. To live along with the times, of course, character education should take part in it, one of which is by presenting values of leadership that can be emulated by the current generation, such as those of one of the Prophet's companions, namely Caliph Umar bin Khattab. This research uses literature study research methodology, which is the process of collecting materials related to research from books, journals, literature, and other publications that deserve to be used as sources for further research by the author. As a result, several values of leadership Umar bin Khattab can be emulated because they are considered relevant to the current moral condition of Gen Z, namely the value of Umar bin Khattab's religiosity in embracing Islam and always struggling in da'wah, the value of his courage in upholding justice, upholding high tolerance values between religious communities, holding the principle of simplicity in the midst of the wealth he has, and always working hard by exerting all the efforts he has without getting tired.